The Rise of the Corporation in a Craft Industry: Conflict and Conformity in Institutional Logics - Thornton, Patricia (Academy of Management Journal, 2002)
This study tests a theory of how a craft- and profession-based industry adopted multidivisional organization, examining higher education publishing from 1958 through 1990. I combined interviews and historical analysis to identify two institutional logics, an editorial and a market logic. Hazard rate models of differences in the effects of these logics showed a decrease in the importance of professional determinants of organization structure and an increase in the salience of its market determinants. The covariates explaining the rate at which firms divisionalized changed as a consequence of their strategic and structural conformity with the prevailing institutional logic.